2020
DOI: 10.1108/bjm-02-2019-0079
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable crowdfunding: insights from the project perspective

Abstract: PurposeThis paper explores the peculiarities of sustainable crowdfunding from the project perspective. The research question is: what are the distinctive features of sustainable crowdfunding, in terms of crowdfunding motivation, platform choice, crowdfunding costs and relationships with backers?Design/methodology/approachThe current study follows a qualitative approach, through conducting in-depth interviews with representatives of sustainable projects, which have had successful crowdfunding campaigns. The sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…The newest findings confirmed that altruism can bridge the value-action gap for green brands (Panda et al , 2020). Research suggests that sustainable entrepreneurs, (including ecoprenuers) need to place more effort in communicating with potential investors to compensate for the intangibility of sustainable claims (Maehle, 2020), as the social and environmental values delivered by the venture may not always be explicit or self-explanatory. To conclude, despite the growing research devoted to the phenomenon of crowdfunding, the aspects of financing eco-investments are vague.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The newest findings confirmed that altruism can bridge the value-action gap for green brands (Panda et al , 2020). Research suggests that sustainable entrepreneurs, (including ecoprenuers) need to place more effort in communicating with potential investors to compensate for the intangibility of sustainable claims (Maehle, 2020), as the social and environmental values delivered by the venture may not always be explicit or self-explanatory. To conclude, despite the growing research devoted to the phenomenon of crowdfunding, the aspects of financing eco-investments are vague.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, in equity crowdfunding, this finding is not confirmed (Vismara, 2019). Whilst sustainability is relevant [5] for all four crowdfunding models, loan-based projects seem to have the highest success rates in relation to sustainability [6] (Maehle, 2020). We, thus, hypothesise that ES and social sustainability (SS) is also important for the success of fashion crowdfunding calls given the pressure this sector faces for more responsible production processes.…”
Section: Crowdfunding Environmentally and Socially Sustainable Productsmentioning
confidence: 95%
“…Following the Rana Plaza collapse in Bangladesh in 2013, a fashion revolution was initiated to push consumers to adopt more sustainable fashion practices and demand greater transparency and control over the entire supply chain [4]. Within crowdfunding literature, sustainability (social and environmental) is not predominant in the empirical analyses, but it has gauged more attention recently (Motylska-Kuzma, 2018;Wehnert et al, 2019;Maehle, 2020). A few empirical studies show how projects with sustainable characteristics are more successful (Calic and Mosakowski, 2016) and often develop better messages in their campaign (Maehle, 2020).…”
Section: Crowdfunding Environmentally and Socially Sustainable Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing focus among researchers on crowdfunding of sustainable projects, such as for example Tenner & Hörisch (2021) studying investor characteristics in sustainable crowdfunding; Maehle et al (2021) analyzing the use of climate frames in crowdfunding campaigns; Maehle (2020) studying the distinctive features of sustainable crowdfunding; and Testa et al (2019) connecting sustainable crowdfunding with Multi Level Perspective (MLP).…”
Section: Introductionmentioning
confidence: 99%